Comparing long-term outcomes between laparoscopic sleeve gastrectomy and Roux-en-Y gastric bypass for morbid obesity - Pattharasai Kachornvitaya; Sikarin Sornphiphatphong; Komol Chaivanijchaya; Fon Pakul; Suthikiat Joradol; Patchaya Boonchaya-Anant; Suthep Udomsawaengsup (Asian Journal of Surgery)
Summary: Background: Laparoscopic sleeve gastrectomy (LSG) and laparoscopic Roux-en-Y gastric bypass (LRYGB) are the two most bariatric procedures in Asia. However, a comparison of long-term outcomes is still limited. Objectives: To compare the degree of long-term weight loss, remission of comorbidities and complication rates after LRYGB and LSG procedures. Methods: A retrospective analysis was conducted for all patients who underwent LSG or LRYGB between May 2005 and May 2018 at a single institute with at least 1–5 years of follow up. Demographic data were collected. Results: Of the total 342 patients, 159 underwent primary LSG and 183 patients underwent LRYGB. Preoperative BMI in the LSG group was significantly higher than the LRYGB group (54.7 ± 12.6 kg/m2 vs 48.2 ± 8.2 kg/m2, P = 0.001). Comorbidities between LSG and LRYGB groups were similar. Mean percentage of total weight loss (%TWL) at 5 years after was 23.6 ± 1.7 % in the LSG group vs. 29.9 ± 1.3 % in the LRYGB group (P = 0.005) and LRYGB resulted in greater weight loss than LSG at all time points. The remission of comorbidities were similar in both groups, except that dyslipidemia was significantly better in the LRYGB group. Overall complications were 35.2 % in the LSG group vs. 20.8 % in the LRYGB group (P = 0.003). Conclusions: Our center revealed that LRYGB had better results than LSG in terms of percentage total weight loss at all time points. In the long term, LSG showed a higher overall complication rate compared to LRYGB.